GOVERNANCE, THE PLIGHT OF THE ELDERLY AND THE SEARCH FOR AN INCLUSIVE SOCIAL ORDER IN NIGERIA - Musa, Muhammad Nurudden; Yunusa, Aminu; Idris, Abdulrahman (African Journal of Social and Behavioural Sciences, 2025)
The increasing search for a better life for the elderly in Nigerian society makes it imperative to explore the link between governance and the plight of the elderly as a way of building an inclusive social order. Through governance, which entails the deployment of an administrative system to regulate components of society for the purpose of promoting inclusiveness, the plight and peculiarities of the elderly could be improved in order to attain a more humane social order. This paper relies on the qualitative description analysis predicated on the use of secondary data to project governance as a driver for the improvement of the plight of the elderly in the country. This paper, which adopts the Social Exchange Theory, finds that poor governance reflected in the failure to deploy available machinery to cater for the needs of the elderly result in the deplorable social well-being of the aged in Nigeria. The paper recommends, among others, the deployment of governance structure and the machineries toward the betterment of the wellbeing of the elderly. These should manifest in timely payment of pension benefits, expansion of access to healthcare, and creation of more legislation on a wide range of issues that could provide a durable cover for the elderly in Nigerian society.